Sovereign determination or disguised protectionism? the Vitamin C Case - Abrenica, Ma. Joy (Philippine Review of Economics, 2019)
When a sovereign state vouches for the anti-competitive behaviour of its producers, it is incumbent upon the courts to abstain from adjudicating and allow economic diplomacy to take its course. The recent decision of the US Supreme Court on a cartel case involving Chinese exporters of vitamin C appears to favour pro-active judicial enforcement of antitrust law, however. Comity among nations calls for giving due deference to the legitimate choices of others with respect to regulating competition in their own industries. But a state harmed by the anti-competitive conduct of foreign producers faces the difficult choice between protecting its own interest and avoiding intrusion into the conduct of another sovereign state. This paper explores this conundrum, which has implications on states with a development agenda that subordinates competition to industrial goals.